DI-080 Drug interactions with oral antineoplastic agents. (24th February 2014) - Ribed, A; Escudero-Vilaplana, V; Sanchez-Fresneda, MN; Sarobe, C; Romero-Jiménez, RM; Bravo-Lázaro, M; Marquínez-Alonso, I; Ruiz, C; Monje, B; Sanjurjo-Sáez, M
Abstract : Background: Oral antineoplastic agents (OAA) interact with cytochrome P450. Therefore, one of the most important objectives of pharmaceutical care in cancer patients, who are usually polymedicated, is to review and identify drug interactions. Purpose: To describe drug interactions detected in a Pharmaceutical Care Programme applied to patients who are starting treatment with OAA. Materials and methods: An observational study was performed in patients who started treatment with OAA during the study period (January 2012 – August 2013). At the time of starting treatment, a clinical interview was conducted by the pharmacist, in order to detect drug interactions. Subsequently, prescriptions and reports from all patients were reviewed and interactions analysed using Lexicomp. Variables recorded were: gender, age, ECOG performance status, type and dose of OAA, other chronic treatment and interactions and their severity classified according to the FDA. Results: 121 patients were included (62.0% male). The mean (SD) age was 67.9 (14.3) years old and 9.9% had an ECOG ≥2. The main OAA dispensed were: abiraterone (19.0%), lenalidomide (18.2%), sunitinib (11.6%), gefitinib (10.7%), imatinib (9.1%) and sorafenib (9.1%). The mean number of chronic co-medications used was 5.0 (2.1). Seventy two interactions were identified in 49 different patients, 27.8% had category D or X. Interactions were more prevalent with abiraterone (41.7%), gefitinib (16.7%) and imatinib (13.9%). Principal groups of drugs interacting with OAA were proton pump inhibitors (25.0%), antihypertensives (24.8%), statins (15.3%) and antidepressants (8.3%). Principal drugs interacting were amlodipine (11.1%), rabeprazole (8.3%), acenocoumarol (8.3%), atorvastatin (6.9%), simvastatin (6.9%) and tramadol (5.6%). The pharmacist was involved by informing the patient and the physician and monitoring the interaction in the follow-up. Conclusions: Abiraterone is the OAA with most identified interactions. It is essential to review all the chronic drugs before starting a new OAA; be careful especially with proton pump inhibitors and antihypertensives. No conflict of interest.